PENGARUH KONDISI TAJUK DAN APLIKASI GETAR TERHADAP PRODUKSI NIRA AREN DI REJANG LEBONG BENGKULUPlant sugar palm (Arenga pinnata) is a plant that provides economic benefits, social, and conservation. Nira is one of the sugar plant products of high economic - Enggar Apriyanto; Dedi Setiadi (Jurnal Pertanian Tropik, 2016)
Plant sugar palm (Arenga pinnata) is a plant that provides economic benefits, social, and conservation. Nira is one of the sugar plant products of high economic value. The research objective was to determine the effect the condition header tanamaan juice and shakes application to the production of sap. The study was conducted in October and November 2015. Materials and tools used in the study is the sugar plant, jerry cans shelters sap, a knife to cut manggar, hose, refractometer, and digital vibrating tools used machineMetode therapy is a method of observation. Data were collected for the sugar plant with a dense canopy, medium and light. Application shakes performed on plants with dense canopy and as control is a plant that did not receive the application shakes. All treatment was repeated three times. The data obtained were analyzed quantitatively. The results showed that the condition of the plant canopy affect the production of palm sap. Average production of sap in the sugar plant with a dense canopy, moderate, and lacking in a row as much as 12.50, 9.13, and 4.56 liter per day. Application shakes 2 times for 15 minutes in the morning and afternoon were able to increase production 67% juice, where the total production of the juice for 18 days leads to the receiving application manggar shakes and controls are 236.3 and 141.6 L / plant. The average sugar content in the sap of approximately 16% brix.